Application of the Principle of Transparency in the Law Enforcement Process (Analysis of the Vina Cirebon Case) - Devi Rakhmatika (Kosmik Hukum, 2024)
In 2016, the murder cases of Vina and Eky in Cirebon occurred, where both were victims of murder and abuse by a group of motorcycle gangs. The case revealed that 11 people were named as suspects, with eight of them receiving prison sentences. However, three other suspects are still on the wanted list. The public questioned the credibility of the police in handling this case. Transparency in law enforcement in Indonesia is essential, which means publicly accessible information about the processes and outcomes of government administration. This transparency also includes criminal investigations by the police who must issue an online notice of progress of investigation (SP2HP). However, there are eight types of information that are exempt from being confidential, including the identity of victims and witnesses. In the handling of Vina's case, the victim's family felt that they did not receive adequate transparency, as it was difficult to obtain information on the progress of the case and access to evidence such as Vina's cell phone. After eight years, the public demanded the arrest of DPOs, but the police announced that only one suspect was at large, leading to doubts and speculation in the community. In conclusion, applying the principle of transparency in law enforcement is crucial to achieving substantive justice. In Vina's case, the lack of transparency made the public doubt the credibility of law enforcement and complicated the resolution of the case. Law enforcers must adhere to established moral values and standard operating procedures (SOPs) to maintain institutional integrity and provide the information needed by the victim's family in accordance with their rights under the law.Keywords: Principles of Openness/Transparency, Law, Crime